Rational expectations models with anticipated shocks and optimal policy: a general solution method and a New Keynesian example - Hans-Werner Wohltmann; Roland C. Winkler (Kiel Institute for the World Economy (IfW), 2009)
The purpose of this paper is to show how to solve linear dynamic rational expectations models with anticipated shocks by using the generalized Schur decomposition method. Furthermore, we determine the optimal unrestricted and restricted policy responses to anticipated shocks. We demonstrate our solution method by means of a micro-founded hybrid New Keynesian model and show that anticipated cost-push shocks entail higher welfare losses than unanticipated shocks of equal size.
Keywords: C61; C63; E52; 330; Anticipated Shocks; Optimal Monetary Policy; Rational Expectations; Generalized Schur Decomposition; Welfare Effects; Schock; Rationale Erwartung; Ungleichgewichtstheorie; Mikroökonomische Fundierung; Dynamisches Modell; Dekompositionsverfahren; Geldpolitik; Wohlfahrtseffekt; Theorie